Article Index

Mas Ecuaciones Simples, agregamos paréntesis

 

21) 5(x + 3) = 12

22) 22(2x - 8) = 3

23) 12 - 3(-5 + 2x) = 9

24) 9 + 5(x + 5 -3x) = 12

25) 4 - 2 + (x + 1) = 9

26) 22 + 20 -(2x + 3) = 7

27) 15 - 9 + (3x + 8) = 22

28) 5x - 3(9x - 7) = -8 + 4x

29) 6 + 12(x - 10) = -3 + 12x

30) 6(2x - 3) = 3x -2x

31) (x + 5)5 = 13x + 8

32) 13x + 20 = 16(x + 4) + 3

33) 6x + 25x -(3 + 2x) = 6 + 3x

34) (5 + x) + 3 = 12x + 8

35) 6x + 3x = 7(2x + 2 + 5x)

36) 13 = 10(x - 3x + 2)

37) 8x - 3 = (x + 5)

38) 19x + 3x = 5x(4 + 3)

39) 20 + 6x = - 21(13x - 8x)

40) 16x + 8x = 3(5x + 1)

Additional information